Hydro-Physical Properties of Soils under Different Land Uses in Northeastern Nigeria - Ibraheem Alhassan; Muhammad Saddiq Askira (Turkish Journal of Agriculture: Food Science and Technology)
Evaluation of soil hydro-physical properties is very important in agriculture and for sustainable management of the land resources. This investigation was conducted to assess some hydro-physical properties of soils in different land use types (LUT) selected (i.e., dry upper land (UD), lowland (LL) and residential area (RA)) at 0-15cm and 15-30cm depths in Bade Local Government Area of Northeastern, Nigeria. Soils were randomly sampled at four points in each LUT and analyzed according to standard soil analysis procedures. Results of the analyses of variance showed that LL had recorded significantly higher clay content, larger soil porosities and high-water retention properties than the other LUT. Soil structural stability index (SSI) and organic carbon (OC) were below optimal range and statistically not different across the land uses. The results also indicated non-significant differences in the hydro-physical properties within the sampling depths. The coefficient of variation (CV) revealed that, slight variation (CV